(6x^2 -x+2)(6x^2+3x+2)=96x^2 giúp mk vss mk cảm ơn ạ!!!

By Remi

(6x^2 -x+2)(6x^2+3x+2)=96x^2
giúp mk vss mk cảm ơn ạ!!!

0 bình luận về “(6x^2 -x+2)(6x^2+3x+2)=96x^2 giúp mk vss mk cảm ơn ạ!!!”

  1. Đáp án:

    $S = ${$ \dfrac{9±\sqrt[]{33}}{12}, \dfrac{-11±\sqrt[]{73}}{12}$}

    Giải thích các bước giải:

    $(6x^2-x+2).(6x^2+3x+2) = 96x^2$ (1)

    $ĐKXĐ : x ∈ R$

    Đặt $6x^2+2+x = a.$ Khi đó pt (1) trở thành :

    $(a-2x).(a+2x) = 96x^2$

    $⇔a^2-4x-96x^2=0$

    $⇔a^2-(10x)^2 = 0 $

    $⇔(a-10x).(a+10x) = 0 $

    $⇔ \left[ \begin{array}{l}a-10x=0\\a+10x=0\end{array} \right.$

    $⇔ \left[ \begin{array}{l}a=10x\\a=-10x\end{array} \right.$

    +) Với $a=10x$ thì :

    $6x^2+2+x=10x$

    $⇔6x^2-9x +  2 = 0 $

    $⇔ x = \dfrac{9±\sqrt[]{33}}{12}$ ( Thỏa mãn )

    Với $a=-10x$ thì :

    $6x^2+2+x=-10x$

    $⇔6x^2+11x+2=0$

    $⇔x = \dfrac{-11±\sqrt[]{73}}{12}$ ( Thỏa mãn )

    Vậy $S = ${ dfrac{9±\sqrt[]{33}}{12}, \dfrac{-11±\sqrt[]{73}}{12}} $

     

    Trả lời

Viết một bình luận